Financial Autonomy Policy Implementation in Local Government for Grassroots Development in Nigeria - Izokpu, Oikhala Gabriel; Iyoha, Anthony Emhenya; Muhibat , Osungboye Biola (LPPM Universitas Jambi, 2025)
Establishing financial autonomy in Nigeria's local government system is a critical component of ensuring good governance for grassroots development. Despite the constitution's endorsement of local government's competence to lead grassroots development, the financial autonomy policy to enhance the competence has not been implemented. The objective of this paper is to assess the impact of local government financial autonomy policy implementation on grassroots development in Nigeria, analyze the challenges encountered during implementation and give recommendations. Interviews were conducted to gather primary data for this paper, which was then supplemented with pertinent published materials. The data were analyzed using a descriptive method. Using decentralization theory as a theoretical framework, the paper found out that financial autonomy policy is crucial to grassroots growth. This paper identified weak political structures and leadership as barriers to the implementation of local government financial autonomy policies in Nigeria, which have implications for Nigeria’s poor grassroots development. The paper concluded that local government financial autonomy policy execution is important for grassroots development and advocated that Nigeria's political systems and leadership shortcomings be addressed by constitutional revision. This paper also recommended that political leaders in Nigeria should be committed to grassroots development by ensuring that the financial autonomy policy of local governments is effectively enforced.